158k views
5 votes
The 4th and the last terms of an A.P. are 11 and 89 respectively. If there are 30 terms in the A.P., find the A.P. and its 23rd term.​

User Klor
by
5.3k points

1 Answer

9 votes


\underline{\underline{\large\bf{Given:-}}}


\red{\leadsto}\:
\textsf{}
\sf Number \: of \:terms \: in \: A.P,n = 30


\red{\leadsto}\:
\textsf{}
\sf Fourth \: term ,a_4 = 11


\red{\leadsto}\:
\textsf{}
\sf last\:term, a_(30) = 89


\underline{\underline{\large\bf{To Find:-}}}


\orange{\leadsto}\:
\textsf{ }
\sf The \: A.P.


\orange{\leadsto}\:
\textsf{ }
\sf 23rd\: term, a_(23)


\\


\underline{\underline{\large\bf{Solution:-}}}\\

The nth term of A.P is determined by the formula-


\green{ \underline { \boxed{ \sf{a_n = a+(n-1)d}}}}

where


  • \sf a = first \:term

  • \sf a_n = nth \: term

  • \sf n = number \:of \:terms

  • \sf d = common \: difference

Since ,


\sf a_4 = 11


\longrightarrow
\sf a+(4-1) d= 11


\longrightarrow
\sf a+3d= 11\_\_\_(1)


\sf a_(30)= 89


\longrightarrow
\sf a+(30-1)d=89


\longrightarrow
\sf a+29d= 89\_\_\_(2)

Subtracting equation (1) from equation(2)


\begin{gathered}\\\implies\quad \sf a+29d-(a+3d) = 89-11 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf a+29d-a-3d = 78 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf a-a+29d-3d = 78 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf 26d = 78 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf d = (78)/(26) \\\end{gathered}


\begin{gathered}\\\implies\quad \sf d = 3 \\\end{gathered}

Putting the value of d in equation (1) -


\begin{gathered}\\\implies\quad \sf a+3(3) = 11 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf a = 11-9 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf a = 2 \\\end{gathered}

  • First term of A.P, a = 2

  • Second term of A.P.,
    \sf a_2= 2+(2-1)* 3


\quad\quad\quad\sf =2+3


\quad\quad\quad\sf =5

  • Third term of A.P.,
    \sf a_3= 2+(3-1)* 3


\quad\quad\quad\sf =2+6


\quad\quad\quad\sf =8


\longrightarrowThus , The A.P is 2,5,8,. . . . . .

Now,


\begin{gathered}\\\implies\quad \sf a_n = a+(n-1)d \\\end{gathered}


\begin{gathered}\\\implies\quad \sf a_(23 )= 2+(23-1)* 3 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf a_(23) = 2+22 * 3 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf a_(23) = 2+66 \\\end{gathered}


\begin{gathered}\\\implies\quad \sf a_(23) = 68 \\\end{gathered}


\longrightarrowThus , 23rd term is 68.

User PawanS
by
5.2k points